Implementasi Kebermanfaatan dalam Teori Utilitarianisme Melalui Pemidanaan Anak di Lembaga Pembinaan Khusus Anak (LPKA) - Wahyu Sinta Dewi Pramudita; Ali Masyhar Mursyid; Cahya Wulandari (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines criminal responsibility in the context of utility through LPKA policy, motivated by the increasing involvement of children in deviant behavior that requires a humanistic approach to rehabilitation. Using a legal-normative method with a legal and theoretical approach, the study analyzes the implementation of Jeremy Bentham's utilitarianism in the child rehabilitation system. The results indicate that LPKA has adopted the principle of utilitarianism through a paradigm shift from retributive to restorative, reflected in comprehensive rehabilitation programs encompassing education, skills training, and psychosocial support. However, optimal implementation is hindered by resource constraints and an inadequate evaluation system. The study recommends the development of a sustainable evaluation mechanism that includes long-term indicators to measure effectiveness in accordance with utilitarianism principles.